Do interspecific image-based ageing guides produce accurate estimates of nestling ages? – progress toward development of a generalised ageing guide. Issue 2 (3rd July 2017) - Brown, William P.; Alianell, Tessa W.
ABSTRACT: Image-based ageing guides of passerine nestlings can produce accurate age estimates. If different species develop similarly, but timing of development differs, creation of a generalised image-based ageing guide for use with nestlings of multiple species is justified if age estimates can be corrected to account for such differences of timing. To explore this idea, inexperienced participants used an image-based ageing guide for Tree Swallow Tachycineta bicolor nestlings to produce age estimates from images of known-age nestling Eastern Bluebirds Sialia sialis and House Wrens Troglodytes aedon . Participants also used a House Wren ageing guide to produce age estimates of nestling Eastern Bluebirds and an Eastern Bluebird ageing guide to produce age estimates of House Wren nestlings (n = 54 total participants and 2565 age estimates). Ages of nestling bluebirds were generally underestimated with the swallow and wren ageing guides, while ages of wrens were generally overestimated with the swallow and bluebird guides. Although the accuracy of age estimates (the percentage within one day of actual age) produced by interspecific guides ranged from 43% to 77% overall, accuracy of estimates corrected using regression analyses increased to better than 80% for all pairwise comparisons. Based on these results, continued development and refinement of a generalised nestling ageing guide is warranted.